Keep it simple, stupid!: The determinants of language complexity in politicians' parliamentary and online communication - Rebecca Kittel; Bruno Castanho Silva (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2026)
Politicians can adjust the complexity of their communication to signal different things to different audiences: more complex language can indicate competence, while lower complexity may bring them closer to "common people". These strategic shifts in complexity, however, remain understudied. We ask what individual and contextual factors relate to politicians' use of more or less complex language in their communication, with a dataset matching 116,000 parliamentary speeches from 15 countries with 800,000 contemporaneous Facebook posts from the same MPs between 2018 and 2021, and apply measures of language complexity to each. Results show that women use more complex language in parliament, and that far-right politicians, while similar to others in parliamentary speech, simplify their language the most on social media, and benefit the most from higher engagement with their simpler posts. These results show new dimensions of how politicians strategically adapt their communication styles to the audience.
Keywords: 330; Language Complexity; Strategic Communication; Parliamentary Discourse; Social Media; Political Communication